Validation, Invariance, and Reliability of Instruments for the Assessment of Knowledge and Attitudes Toward Cardiopulmonary Resuscitation in Peruvian Children and Adolescents - Ángel López-González; Joseba Rabanales-Sotos; Yrene E. Urbina-Rojas; Zoila E. Leitón-Espinoza; María D. P. Gómez-Luján; Francisco García-Alcaráz; Walter Capa-Luque (Children)
Background/Objectives: In this study, we aimed to analyze the validity, based on the internal structure of the construct, measurement invariance by sex, and reliability of the scores for the “Knowledge in Basic Cardiopulmonary Resuscitation in Peruvian children/adolescents” (KBCPR_P21) and “Attitudes in Basic Cardiopulmonary Resuscitation in Peruvian children/adolescents” (ABCPR_P21) instruments in Spanish. Methods: A cross-sectional and instrumental methodological study was conducted between February and August 2021, with the participation of 415 Peruvian elementary school students between 8 and 13 years of age. Participants responded to surveys on knowledge and attitudes toward CPR. For both instruments, exploratory factor analysis (EFA) and confirmatory factor analysis (CFA) was used as the estimation method for categorical data. Results: All of the items for both scales have high discriminative capacity (>0.30), and both scales showed high internal consistency (Cronbach’s alpha > 0.87 and McDonald’s omega > 0.90). The validity, based on the internal structure of the construct, implied the existence of a single factor grouping all the items in the two scales (CFI and TLI > 0.95; RMSEA and SRMR < 0.08). Multigroup confirmatory factor analysis also allowed us to satisfactorily verify measurement invariance by sex at the four levels (configural, metric, scalar, and strict) for both scales. Conclusions: We can conclude that the values obtained in our evaluation of the scales favor considering them as valid and reliable instruments with which to measure knowledge and attitudes toward basic cardiopulmonary resuscitation in children/adolescents in Peru, given prior learning. The scales could also be used in the evaluation of knowledge and attitudes around basic cardiopulmonary resuscitation in other countries, providing trainers with rapid feedback on the knowledge and attitudes transmitted in training courses, thus allowing better control over the training activities carried out in these courses. Finally, the availability of the scales would allow researchers to empirically test their psychometric properties in other countries.